Informal Health Education for Early Childhood in Indonesia - Siswanto, Hadi (EDUCARE, 2009)
ABSTRACT: The spurting growth and development of early childhood are usually identified as a golden time, the window of opportunity and critical period as well. It needs appropriate and optimum method of caring for loving and teaching in informal education. This informal health educational program is accomplished by parenting method, primary health care, adequate nutrition intake and healthy environment. Breastfeeding, including early breastfeeding program as well as exclusive breastfeeding, adequate nutrition intake, healthy environment, disease prevention, healthy house and utilization of sanitation as healthy and clean life behavior are contents of informal health education for early childhood. Stimulation and embrace from mother provide satisfaction and secure feeling to baby. Motherâs instinct to educate through learning-by-doing method, supported by knowledge and skill to maintain health, disease and nutrition control, healthy house and environment, healthy life behavior and nutrition awareness will complete the education in concrete situation. Healthy and clean life behavior are vice versa healthy environment. Family members and parents, especially mother, have roles, functions and responsibilities in informal health education. This article purposes to provide information and present materials and how informal health education is implemented as well as the role and importance of parenting in growth and development of early childhood in Indonesia.KEY WORDS: informal education, early childhood, growth spurt and development, nutrition, healthy environment and healthy life.About the Author: Dr. Hadi Siswanto, S.K.M., M.P.H. is a Lecturer and Dean of the Faculty of Health Science URINDO (University of Respati Indonesia), Jalan Bambu Apus I No.3 East Jakarta, Indonesia. He can be reached at: hadisis_viva@yahoo.comHow to cite this article? Siswanto, Hadi. (2009). âInformal Health Education for Early Childhood in Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.219-232. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 14, 2008); Revised (January 18, 2009); and Published (February 17, 2009).